Article Review: Diagnosis dan Tatalaksana Rhinitis Medikamentosa - Rahmi Zuraida; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Rhinitis medicamentosa (RM) is a condition caused by overuse of nasal decongestants. This can be seen when patients use topical decongestants for more than 5 consecutive days and are accompanied by symptoms of persistent nasal congestion and secretions. The term rhinitis medicamentosa is also called rebound or chemical rhinitis. In addition, rhinitis medicamentosa is also a term for nasal congestion after using drugs other than topical decongestants. These drugs are antihypertensives, antipsychotics, PDE5 inhibitors, analgesics, hormones, and miscellaneous. However, there are differences in the mechanism through which congestion is caused by topical nasal decongestants and oral medications. Very few prospective rhinitis medicamentosa studies have been conducted and most of the knowledge about the condition comes from case reports and histological studies. Histologic changes consistent with rhinitis medicamentosa include nasociliary loss, squamous cell metaplasia, epithelial edema, epithelial cell denudation, goblet cell hyperplasia, increased epidermal growth factor receptor expression, and inflammatory cell infiltration. Because the cumulative dose of nasal decongestants or the length of time needed to start rhinitis medicamentosa has not been definitively determined, these medications should only be used for the shortest period needed. Validated criteria need to be developed and further tests also need to be carried out to establish a better diagnosis. Stopping nasal decongestant use is the first line of treatment for rhinitis medicamentosa. If necessary, intranasal glucocorticosteroids should be used to speed recovery.